Predicting water availability in irrigation tank cascade systems: the cascade water balance model - Jayatilaka, C.J.; Sakthivadivel, Ramaswamy; Shinogi, Y.; Makin, Ian W.; Witharana, P. (International Water Management Institute, 2001)
Better water management in irrigation tank cascade systems is vital in achieving higher productive use of available water. To develop and implement management practices aimed at improving effective use of water, studies leading to the development of models that can predict available tank water in irrigation tank cascade systems are invaluable. This report presents a simple water balance model, Cascade, developed to predict tank water availability in the Thirappane tank cascade system in Anuradhapura, Sri Lanka. The report includes calibration of the model and its application to predict tank water availability for rice crops over a 10-year period.